2019
DOI: 10.14311/ap.2019.59.0042
|View full text |Cite
|
Sign up to set email alerts
|

Welding of Nitinol by Selected Technologies

Abstract: Nitinol is a perspective alloy that is difficult to weld because of its high sensitivity to heat, atmospheric gases and the NiTi phase instability. We evaluated several welding techniques with regard to their applicability to weld fine pseudoelastic NiTi wires. Namely, we tested the microplasma arc, laser, electron beam, resistance and capacitor discharge welding. In conclusion, the behaviour of the weld for any of the implemented welding techniques is similar; it leads to a loss of mechanical properties in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In accordance with studies in the literature, a similar trend of decrease in UTS value and increase in percent elongation was reported in Nitinol joints welded using TIG, µPAM, LBW, EBW, resistance welding, and CDW processes. 9,18,19 In earlier studies in literature, LBW of Nitinol showed a larger reduction in UTS value of 39-52%. 17,18 Compared to the UTS value of BM, sample P (111.25 J/mm) and sample S (120.14 J/mm) showed 19.14% and 32.29% decrease in UTS value, respectively.…”
Section: Metallurgical Characterizationmentioning
confidence: 80%
See 1 more Smart Citation
“…In accordance with studies in the literature, a similar trend of decrease in UTS value and increase in percent elongation was reported in Nitinol joints welded using TIG, µPAM, LBW, EBW, resistance welding, and CDW processes. 9,18,19 In earlier studies in literature, LBW of Nitinol showed a larger reduction in UTS value of 39-52%. 17,18 Compared to the UTS value of BM, sample P (111.25 J/mm) and sample S (120.14 J/mm) showed 19.14% and 32.29% decrease in UTS value, respectively.…”
Section: Metallurgical Characterizationmentioning
confidence: 80%
“…In comparison with the BM, welded samples exhibit a 39.13% fall in tensile strength, while the elongation percentage of welded NiTinol joints was reduced by 2%. Kramar T et al 19 joined NiTinol using micro-plasma arc welding (µPAM), LBW, electron beam welding (EBW), resistance welding, and capacitor discharge welding (CDW). The authors observed better tensile strength in LBW compared to other welding processes owing to the lesser intermetallic phase formation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a complex, three-dimensional structure of an implant, an appropriate method of forming and connecting elements or their fragments is necessary. There are several techniques of joining NiTi alloys, including: plasma welding [ 11 ], vacuum brazing [ 12 ], resistance welding [ 13 ], tungsten inert gas [ 14 ], friction welding [ 15 , 16 ], microplasma arc welding [ 15 ], capacitor discharge welding [ 15 ], explosive welding [ 16 ], ultrasonic welding [ 16 ], adhesives joining [ 16 ], and laser welding [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, most of these methods are used to join sheets, tubes, tapes, or strips.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys have become highly sought-after due to their outstanding properties, including excellent corrosion resistance, bio-compatibility, non-magnetic nature, as well as impressive mechanical and thermo-mechanical properties. As a result, Nitinol has found numerous applications across a wide range of fields, such as automobile, aerospace, biomedical, robotics, MEMS, sensors and actuators, hydro-space, structural and civil applications [2].…”
Section: Introductionmentioning
confidence: 99%